Deep-Sea-Derived Fungi as Valuable Producers of Cytotoxic Secondary Metabolites and Their Leads Potential - Guangrong Zhao; Wenli Tang; Jianlong Zhang; Peimin Shi; Youzhi Li; Jiao Wang; Qingqin Shen; Haixia Si; Linlin Jiang; Xin Yu; Hongwei Zhu; Guozhong Chen; et al. (Frontiers in Marine Science, 2022)
Cancer is the leading lethal disease worldwide. Natural products have contributed significantly to the development of approved therapeutic agents. Therefore, research into new bioactive naturally sourced metabolites with lead potential is urgently needed. It is well-known that marine microorganisms are by far one of the most notable and prolific sources of bioactive natural products. Among them, deep-sea-derived fungi are extraordinarily adapted and metabolically active under extreme environmental conditions, which enable them to produce a large number of novel secondary metabolites. Chemical examination of deep-sea-derived fungi has yielded enormous amounts of cytotoxic natural products and potential drug leads. This review summarizes a total of 229 cytotoxic compounds isolated from deep-sea-derived fungi from 2010 to 2021. The emphasis is on the unique chemical diversity of these metabolic products, together with their relevant cytotoxic properties. Among the isolated metabolites, 82 compounds have been found to possess moderate to potent cytotoxic activities. Meanwhile, we also highlight some compounds with potent cytotoxicities (namely “star molecules”) considering their high drug lead potential. This review reveals deep-sea-derived fungi as considerable resources for the development of new drugs and the potential of the newly discovered secondary metabolites as valuable antitumor lead compounds.